Ion synthesis and FMR studies of iron and cobalt nanoparticles in polyimides - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
Polyimide foils were implanted with 40 keV Fe+ and Co+ to doses of 0.25-1.5x10(17) ions/cm(2). Electron microscopy studies showed the formation of iron and cobalt nanoparticles in the implanted polymer layer with a thickness of about 70 nm. The size and shape of the ion-synthesized metal nanoparticles depend on the implantation parameters and subsequent thermal annealing. A ferromagnetic resonance (FMR) response was found in the iron-implanted samples as well as in the annealed cobalt and iron samples. The effective magnetization values of the metal/polymer composite layers were extracted from the FMR spectra and plotted as a function of implantation dose. The magnetic properties of the iron and cobalt nanoparticles in polyimide are compared and discussed. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: ion implantation; magnetic nanoparticles; granular magnetic films; ferromagnetic resonance; FERROMAGNETIC-RESONANCE; SPIN DISORDER; FILMS; FE